BARIATRIC SURGERY AND OBESITY: A SYSTEMATIC REVIEW ON THE SOCIOECONOMIC AND DEMOGRAPHIC IMPACT (CIPEEX, 2025)
Objective: This study aimed to identify the role of bariatric surgery in the treatment of obesity. Methods: This is a systematic literature review guided by the question: “What is the role of bariatric surgery in the treatment of obesity?”. To answer this question, 20 original articles published between 2019 and 2024 were selected from PubMed, SciELO, and LILACS. The descriptors used included “cirurgia bariátrica”, “obesidade”, “redução de peso”, “qualidade de vida”, “comorbidades”, “complicações pós-operatórias” and their English equivalents, combined with the Boolean operators “AND” and “OR”. Results: The bariatric techniques Laparoscopic Sleeve Gastrectomy (LSG), Roux-en-Y Gastric Bypass (RYGB), and One-Anastomosis Gastric Bypass (OAGB) resulted in significant weight loss and improvements in quality of life. OAGB proved to be the most effective for long-term weight loss. RYGB provided sustained weight loss and comorbidity resolution but with greater need for nutritional supplementation. LSG showed a higher prevalence of esophagitis and GERD (Gastroesophageal Reflux Disease), while OAGB presented fewer severe complications and better metabolic outcomes. Conclusion: All techniques are effective for managing obesity and comorbidities, each with specific advantages and challenges. The choice must be individualized, with continuous follow-up, especially to prevent nutritional deficiencies in RYGB and OAGB and to manage GERD in LSG.
Keywords: bariatric surgery; obesity; quality of life; postoperative complications